The Role of Dance Associations in the Evolution of Greek Music – Dance Tradition: The Example of “Sygathistos” Dance in Velvedo of Kozani - Filipou, Φίλιππος; Goulimaris, Δημήτρης; Serbezis, Βασίλης; Pitsi, Αθηνά; Genti, Μαρία (Inquiries in Physical Education and Sport, 2009)
The traditional dance, following the changes that Greek society has experienced since the 1950s, has been modified regarding its form as well as its function. These changes are considered the positive outcome and adaptation to the modern reality of local communities and also the fact that dancing clubs have been practising traditional dances consistently. The aim of this paper is to study the evolution of the Greek musical and dance tradition, during the last fifty years, through the example of the “Sygathistos” dance in Velvedo of Kozani. For conducting this research were used topics from ethnological film and also videotaped performances of Lyceum of Greek Women in Athens and “Centres of Open Protection for the Elderly” (COPE) of Velvedo. Furthermore, it was conducted local ethnographical research. For data analysis and for the coming up to conclusion it was conducted comparison research in the form of “Sygathistos” dance in three chronicle periods (1960, 1980, 1998 & 2000), through comparative method and structural-morphological analysis. From data analysis it is concluded important changes in the performing of dance and also in its role in the local society today.